2013
DOI: 10.1186/1756-6606-6-46
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide Y Y1 receptor knockdown modulates activator protein 1-involved feeding behavior in amphetamine-treated rats

Abstract: BackgroundHypothalamic neuropeptide Y (NPY) and two immediate early genes, c-fos and c-jun, have been found to be involved in regulating the appetite-suppressing effect of amphetamine (AMPH). The present study investigated whether cerebral catecholamine (CA) might regulate NPY and POMC expression and whether NPY Y1 receptor (Y1R) participated in activator protein-1 (AP-1)–mediated feeding.MethodsRats were given AMPH daily for 4 days. Changes in the expression of NPY, Y1R, c-Fos, c-Jun, and AP-1 were assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Also, both Y 1 R knockdown or blockade could modulate the expression of NPY indicating the involvement of this receptor in the regulation of NPY‐mediated appetite suppression (Hsieh et al . ). The authors further suggest that Y 1 R might play an essential role that is consistent with the function of the proopiomelanocortin neurons (an anorexigenic transmission), but is opposite to that of NPY neurons (an orexigenic transmission).…”
Section: Psychostimulant Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, both Y 1 R knockdown or blockade could modulate the expression of NPY indicating the involvement of this receptor in the regulation of NPY‐mediated appetite suppression (Hsieh et al . ). The authors further suggest that Y 1 R might play an essential role that is consistent with the function of the proopiomelanocortin neurons (an anorexigenic transmission), but is opposite to that of NPY neurons (an orexigenic transmission).…”
Section: Psychostimulant Drugsmentioning
confidence: 97%
“…In fact, Hsieh et al . () showed that anorectic response of AMPH was related to a decrease of NPY and to an opposite effect on Y 1 R expression, which was upregulated. Also, both Y 1 R knockdown or blockade could modulate the expression of NPY indicating the involvement of this receptor in the regulation of NPY‐mediated appetite suppression (Hsieh et al .…”
Section: Psychostimulant Drugsmentioning
confidence: 98%
“…Neuropeptide Y is a 36-amino acid neuropeptide. Neuropeptide Y receptors are classified into five subtypes: Y1, Y2, Y4, Y5, and Y6 (Hsieh et al, 2013; Mittapalli and Roberts, 2014; Pérez-Fernández et al, 2014). Neuropeptide Y plays functions associated with modulation of food ingestion, mood, learning and memory (dos Santos et al, 2013b) and also plays an important role in neuroprotection against neurodegenerative diseases (Figure 4).…”
Section: Neuropeptide Y and Alzheimer's Diseasementioning
confidence: 99%
“…The NPY‐Y1 receptor has been linked to the regulation of CART neurones by amphetamine‐induced anorexia that increases peptide expression in rats . Another factor likely involved in unchanged CART mRNA levels in this subregion of the PVN in DIA rats is the overexpression of c‐jun and c‐fos (AP1) as in amphetamine‐induced anorexia because the CART promoter has an AP1‐binding site; thus, AP1 might be avoiding a reduction in CART levels as in FFR. This is worthy of study in the DIA model.…”
Section: Discussionmentioning
confidence: 99%